Whoâ€™s Not Afraid of Shakespeare - Melnishka, Mariana (Sledva : NBU Journal of Humanities and Arts, 2020)
The ever growing and updating Shakespearian context is the topic of this article examining the almost simultaneous appearance (in Bulgaria, 2019) of a book, a film, and a theatre production related to the Bard: the book is â€œNothing Like the Sunâ€ by Anthony Burgess (translated by M. Melnishka), the film is Kenneth Branaghâ€™s â€œAll Is Trueâ€, and the theatre production is â€œRomeo and Julietâ€ at the Mladezhki Theatre (Youth Theatre) in Sofia.